2015
DOI: 10.1016/j.ihj.2015.10.375
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effect of percutaneous transvenous mitral commissurotomy on atrial electromechanical delay and P-wave dispersion in patients with severe mitral stenosis

Abstract: Successful PTMC has a favorable early impact on inter- and intra-atrial electromechanical delays, which are considered as novel parameters of atrial electromechanical remodeling in MS patients. Prospective large-scale studies are required to confirm whether improvement in these markers translates into reduced long-term AF risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
3
0
2
Order By: Relevance
“…Successful PTMC has a favorable early impact on inter and intraatrial electromechanical delays, which are considered as novel parameters of atrial electromechanical remodeling in MS patients [11].…”
Section: Normal Limit Values Of P-wave Dispersion (Pwd)mentioning
confidence: 99%
“…Successful PTMC has a favorable early impact on inter and intraatrial electromechanical delays, which are considered as novel parameters of atrial electromechanical remodeling in MS patients [11].…”
Section: Normal Limit Values Of P-wave Dispersion (Pwd)mentioning
confidence: 99%
“…Similar to our results; successful PMBV procedure results in a decrease in PWD. The decline of PWD immediately after PMBV was not supported by Beig et al [15] ; they found statistically significant decrease in inter and intraatrial electromechanical delays. Prolongation of P-wave duration and increased PWD were correlated with increased AF risk according to previous studies [5,16] .…”
Section: Resultsmentioning
confidence: 81%
“…Se ha realizado una amplia investigación clínica de la dispersión de la onda P en el análisis del riesgo de fibrilación auricular en pacientes sin cardiopatía orgánica, en pacientes con enfermedad coronaria, en pacientes sometidos a cirugía de derivación coronaria, en pacientes con cardiopatías congénitas, así como en otros grupos de pacientes que padecen diversas enfermedades cardiacas o no (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) cardiacas . En consecuencia, la PWD puede ser útil para discriminar a pacientes con diferentes tipos de enfermedades que son propensas a desarrollar FA (31)(32)(33)(34)(35)(36) paroxística en el curso de sus vidas .…”
Section: Discussionunclassified